An endogenous Taylor condition in an endogenous growth monetary policy model - Mai Vo Le; Max Gillman; Patrick Minford (Cardiff University, Cardiff Business School, 2007)
The paper derives a Taylor condition as part of the agentís equilibrium behavior in an endogenous growth monetary economy. It shows the assumptions necessary to make it almost identical to the original Taylor rule, and that it can interchangably take a money supply growth rate form. From the money supply form, simple policy experiments are conducted. A full central bank policy model is derived that includes the Taylor condition along with equations comparable to the standard aggregate-demand/aggregate-supply model.
Keywords: 330; Geldpolitik; Geldangebot; Taylor-Regel; Neue Wachstumstheorie; Theorie